Hill classification is superior to the axial length of a hiatal hernia for assessment of the mechanical anti-reflux barrier at the gastroesophageal junction - Hansdotter, Ida; Björ, Ove; Andreasson, Anna; Agreus, Lars; Hellström, Per; Forsberg, Anna; Talley, Nicholas J.; Vieth, Michael; Wallner, Bengt (Endoscopy International Open, 2016)
Background and study aims: The pathogenesis of gastroesophageal reflux disease (GERD) is multifactorial, including the mechanical anti-reflux barrier of the gastroesophageal junction. This barrier can be evaluated endoscopically in two ways: by measuring the axial length of any hiatal hernia present or by assessing the gastroesophageal flap valve. The endoscopic measurement of axial length is troublesome because of the physiological dynamics in the area. Grading the gastroesophageal flap valve is easier and has proven reproducible. The aim of the present study was to compare the two endoscopic grading methods with regard to associations with GERD.Patients and methods: Population-based subjects underwent endoscopic examination assessing the axial length of hiatus hernia, the gastroesophageal flap valve using the Hill classification, esophagitis using the Los Angeles (LA) classification, and columnar metaplasia using the Z-line appearance (ZAP) classification. Biopsies were taken from the squamocolumnar junction to assess the presence of intestinal metaplasia. Symptoms were recorded with the validated Abdominal Symptom Questionnaire. GERD was defined according to the Montreal definition.Results: In total, 334 subjects were included in the study and underwent endoscopy; 86 subjects suffered from GERD and 211 presented no symptoms or signs of GERD. Based on logistic regression, the estimated area under the curve statistic (AUC) for Hill (0.65 [95 %CI 0.59 – 0.72]) was higher than the corresponding estimate for the axial length of a hiatal hernia (0.61 [95 %CI 0.54 – 0.68]), although the difference was not statistically significant (P = 0.225). Conclusion: From our data, and in terms of association with GERD, the Hill classification was slightly stronger compared to the axial length of a hiatal hernia, but we could not verify that the Hill classification was superior as a predictor. The Hill classification may replace the axial length of a hiatal hernia in the endoscopic assessment of the mechanical anti-reflux barrier of the gastroesophageal junction.